The direct and indirect effects of the COVID-19 pandemic on the mental health of confined youth - Lin Liu (Health & Justice, 2024)
Abstract The COVID-19 pandemic posed an unprecedented threat to the mental health of youth due to its attendant, drastic changes in everyday life brought about by restrictions such as social distancing and the cancelation of in-person classes. Although numerous articles have discussed the impact of the pandemic on youths’ mental health, most of them have been opinion pieces. This study used state-wide empirical data to quantify the direct and indirect effect of the pandemic on the mental health of confined youth, a vulnerable social group that is rarely represented in school survey data. Group comparisons of youth who entered juvenile justice facilities during pandemic and non-pandemic times were also conducted. Findings revealed that youth who entered residential facilities during the pandemic due to criminal offenses had higher rates of prior mental health problems and victimization. With major confounders controlled, multivariate regression results showed that the impact of the pandemic on confined youths’ mental health is indirect: it conditioned the effect of underage drinking on the youths’ mental health. Youth who were admitted into facilities during the pandemic were more likely to experience mental health problems than their peers who entered facilities during non-pandemic times. Implications for policymaking are discussed.